2019
DOI: 10.1177/0272431619858397
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Family and Community Violence on African American Adolescents: The Roles of Violence Type and Relationship Proximity to Violence

Abstract: The current study examined the unique and interactive effects of family and community violence across types of violence (weapon, physical, and death) and relationship proximity (self, family/friend, and strangers) in African American adolescents (mean age = 12.63, SD = 0.99, 54% female). Items from the community violence and family violence measures were categorized into a three-factor model of cross-contextual violence exposure that characterized violence by type and relationship proximity. Results of structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
0
26
1
1
Order By: Relevance
“…The literature supports the fact that this is particularly true for African Americans who have historically sought solace from oppression in their religion and spirituality long before clinical counselors and psychologists (Banerjee & Canda, 2009;Cunningham et al, 2018;Johnson et al, 2015;Jones et al, 2018;K. Hays & Aranda, 2016;Robinson et al, 2018;Sargent et al, 2019). The first African American churches were often kept secret, and slaves attended church meetings held at the church under a watchful eye of the overseer, or with the permission of slave masters on plantations by approved pastors (Johnson, Elbert-Avila, & Tulsky, 2015).…”
Section: There Are Historical Connections Of Religion and Spirituality For The African American Populationmentioning
confidence: 80%
See 2 more Smart Citations
“…The literature supports the fact that this is particularly true for African Americans who have historically sought solace from oppression in their religion and spirituality long before clinical counselors and psychologists (Banerjee & Canda, 2009;Cunningham et al, 2018;Johnson et al, 2015;Jones et al, 2018;K. Hays & Aranda, 2016;Robinson et al, 2018;Sargent et al, 2019). The first African American churches were often kept secret, and slaves attended church meetings held at the church under a watchful eye of the overseer, or with the permission of slave masters on plantations by approved pastors (Johnson, Elbert-Avila, & Tulsky, 2015).…”
Section: There Are Historical Connections Of Religion and Spirituality For The African American Populationmentioning
confidence: 80%
“…Other researchers have also found that aggregate adapting and thinking about others and covering of feelings were normal (Chandler, 2020;K. Hays & Lincoln, 2017;Jones et al, 2018;Morrison & Hopkins, 2019;Park et al, 2018;Robinson et al, 2018;Sargent et al, 2019).…”
Section: The Use Of Religion and Spirituality Is A Means Of Coping And Resilience By African Americansmentioning
confidence: 93%
See 1 more Smart Citation
“…These "pair of ACEs" (Ellis and Dietz 2017), combine to act as traumas or "toxic stressors" across one's lifecoursefrom in utero to adulthoodthat adversely impact brain development, decisionmaking, impulse control, and generally wear away at the body's immune system and vital organs (McEwen and McEwen 2017). These pair of ACEs can also cause the brain and body to interpret normal circumstances as dangerous, leading many researchers and practitioners to emphasize the need for healing-centered strategies that explicitly address trauma as a critical aspect of urban gun violence reduction (Ginwright 2018;Hardy 2013;Leitch 2017;Norris 2020;Sargent et al 2020).…”
Section: What Makes Advance Peace Unique In Urban Public Safety?mentioning
confidence: 99%
“…The same study found that knowing the victim did not differentiate among aggressive symptoms. However, a recent study of 403 African American adolescents found that violence directed at friends or family members was associated with higher anxiety, but not PTSD symptoms (Sargent, Zahniser, Gaylord‐Harden, Morency, & Jenkins, ). In a national cross‐sectional sample of 3,614 adolescents, having a personal relationship with the victim of witnessed violence was not associated with higher delinquency symptoms compared to a stranger perpetrator (Zinzow et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%